A population-based study of unintentional injury and premature death among non-imprisoned and imprisoned youth offenders. (January 2023) - Siponen, Rebecca; Andersson, Anneli; Oskarsson, Sofi; Garcia-Argibay, Miguel; Beckley, Amber L.; Långström, Niklas; Fazel, Seena; Chang, Zheng; Larsson, Henrik; Evans, Brittany; Tuvblad, Catherine
Abstract: Background: Youth offenders have a high risk of being injured or dying prematurely. However, few studies have considered the role of imprisonment and potential childhood risk factors for these high rates. Aim: To examine the risk of unintentional injury and premature death in non-imprisoned and imprisoned youth offenders, and to examine the role of parental criminal convictions and psychiatric disorders and own childhood psychiatric disorders. Methods: All individuals ( N = 1, 839, 711) born in Sweden between 1978 and 1996 were identified using Swedish population-based registers. The exposure was criminal conviction between ages 15–20 years of age. Results: Imprisoned youth offenders had the highest risk for unintentional injury (HR = 2.29 [2.19–2.40]) and premature death (HR = 10.76 [9.52–12.16]), followed by nonimprisoned youth offenders, compared to non-convicted youth. All childhood risk factors increased the risk for these outcomes among non-imprisoned youth offenders. Among imprisoned youth offenders, parental criminal convictions and parental psychiatric disorders increased the risk for unintentional injury, and parental psychiatric disorders and own childhood psychiatric disorders increased the risk for premature death. Conclusions: Our study shows there are robust modifiable childhood risk factors for injury and mortality among youth offenders. However, the importance of them to assess risk may differ between non-imprisoned and imprisoned youth offenders. Highlights: Youth offenders had higher risk for injuries and premature death than general youth. Imprisoned youth offenders had higher risk than non-imprisoned youth offenders. Non-imprisoned and imprisoned youth offenders differed in risk-profiles. Childhood risk factors increased the risk in both youth offender groups. Family history of crime and mental illness is important to consider.